The puff-specific RRM protein NonA is a single-stranded nucleic acid binding protein. - Reim, Ingolf; Stanewsky, Ralf; Saumweber, Harald (Chromosoma, 1999)
The chromatin protein NonA from Drosophila, present in many puffs on polytene chromosomes, belongs to the growing class of RRM proteins. Exchange of amino acids within the RNP1 and RNP2 consensus sequences, known from other RRM proteins to be essential for RNA binding, has been shown drastically to reduce NonA function in vivo. Here we compare NonA binding to RNA from the Sgs-4 gene, an in situ target for NonA, with binding to Sgs-3 RNA, which is not a target of NonA. Using an immunoprecipitation assay in vitro we show that NonA binds to single-stranded (ss)DNA and RNA with moderate affinity (KD=8x10(-8) M). However, we did not observe sequence-specific binding to the Sgs-4 transcript nor to Sgs-4 DNA containing upstream regulatory sequences. Point mutations within the RNP1 and RNP2 consensus sequences that interfere with NonA function in vivo do not significantly change chromosomal binding nor the general affinity for RNA. The expression of Sgs-4 RNA relative to the expression of Sgs-3 RNA remains the same in the presence or absence of NonA protein. com/link/service/journals/00412/bibs/108n3p162.html